Effect of Pyrolysis on iron-metal organic frameworks (MOFs) to Fe3C @ Fe5C2 for diesel production in Fischer-Tropsch Synthesis - Munir, Saleem; Amin, Muhammad; Iqbal, Naseem; Iqbal, Amjad; Ghfar, Ayman A. (Frontiers in Chemistry, 2023)
The Fischer-+251Tropsch Synthesis (FTS) is a significant catalytic chemical reaction that produces ultra-clean fuels for improve energy consumption of road vehicles or chemicals with added value from a syngas mixture of CO and H2 obtained from biomass, coal, or natural gas. The presence of sulfur is not considered suitable for producing liquid fuels for Fisher-Tropsch synthesis (FTS). In this study, we reveal that the presence of sulfur in ferric sulfate Fe2(SO4)3 MOF provides a high amount, 52.50% of light hydrocarbons, in the carbon chain distribution. The calcined ferric nitrate Fe(NO₃)₃ MOF reveals the most increased 93.27% diesel production. Calcination is regarded as an essential factor in enhancing liquid fuel production. Here, we probed the calcination effect of Metal-Organic Framework (MOF) on downstream application syngas to liquid fuels. The XRD results of MOF.N and P.MOF.N shows the formation of the active phase of iron carbide (Fe5C2), considered the most active phase of Fischer-Tropsch synthesis. The scanning electron microscopy and energy dispersive spectroscopy (SEM/EDS) images of iron sulfate MOF catalyst (P.MOF.S) reveals that the existence of sulfur creates pores inside the particles due to the reaction of free water molecules with the sulfur derivate. The surface functional groups of prepared MOFs and tested Fourier analyzed MOFS transforms infrared spectroscopy (FT-IR). The thermal stability of prepared MOFS was analyzed by Thermo gravimetric analysis (TGA).